Grave’s Disease with Severe Hepatic Dysfunction: A Diagnostic and Therapeutic Challenge - Ashok Krishna Bhuyan; Dipti Sarma; Uma Kaimal Saikia; Bipul Kumar Choudhury (Case Reports in Medicine)
Hepatic dysfunction in a patient with thyrotoxicosis may result from hyperthyroidism per se, as a side effect of antithyroid drugs, and causes unrelated to hyperthyroidism which sometimes causes diagnostic and therapeutic difficulties. A young female patient was admitted to our hospital with symptoms of thyrotoxicosis, diffuse goiter and ophthalmopathy along with cholestatic pattern of jaundice, and proximal muscle weakness. She was treated with propylthiouracil with gradual recovery. She was continuing her antithyroid medication with regular follow-up. The patient was readmitted a few months later with worsening thyrotoxicosis, proximal muscle weakness, fever, and a hepatocellular pattern of jaundice with sepsis. Propylthiouracil was stopped and lithium along with steroid coverage was given to control her thyrotoxicosis which was later changed to methimazole. Broad spectrum antibiotic therapy was also started but without any response. During her hospital stay, the patient also developed a flaccid paraplegia resembling Guillain-Barre syndrome. IV steroid was started for the neuropathy but meanwhile the patient succumbed to her illness. So in centers where facility for radioiodine therapy is not readily available, some definite well-tested protocols should be formulated to address such common but complicated clinical situations.